2017
DOI: 10.1515/coma-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Strongly not relatives Kähler manifolds

Abstract: Abstract:In this paper we study Kähler manifolds that are strongly not relative to any projective Kähler manifold, i.e. those Kähler manifolds that do not share a Kähler submanifold with any projective Kähler manifold even when their metric is rescaled by the multiplication by a positive constant. We prove two results which highlight some relations between this property and the existence of a full Kähler immersion into the infinite dimensional complex projective space. As application we get that the 1-paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Dealing with the symmetric case, observe that since a Hermitian symmetric space of compact type with integral Kähler form admits a Kähler immersion into some finite dimensional complex projective space, then due to theorems 6.1.1 and This result follows from Theorem 6.2.1 and the following general lemma, which proves that when the Kähler manifold considered is regular, in the sense that it is projectively induced when rescaled by a great enough constant, the property of not being relative to any projective Kähler manifold is invariant by the multiplication of the metric by a positive constant. Lemma 6.2.3 (M. Zedda [82]). Assume that (M, βg) is infinite projectively induced for any β > β 0 ≥ 0.…”
Section: Homogeneous Kähler Manifolds Are Not Relative To Projective mentioning
confidence: 99%
See 1 more Smart Citation
“…Dealing with the symmetric case, observe that since a Hermitian symmetric space of compact type with integral Kähler form admits a Kähler immersion into some finite dimensional complex projective space, then due to theorems 6.1.1 and This result follows from Theorem 6.2.1 and the following general lemma, which proves that when the Kähler manifold considered is regular, in the sense that it is projectively induced when rescaled by a great enough constant, the property of not being relative to any projective Kähler manifold is invariant by the multiplication of the metric by a positive constant. Lemma 6.2.3 (M. Zedda [82]). Assume that (M, βg) is infinite projectively induced for any β > β 0 ≥ 0.…”
Section: Homogeneous Kähler Manifolds Are Not Relative To Projective mentioning
confidence: 99%
“…Cartan-Hartogs domains has been considered by many authors (see e.g. [30,31,50,51,53,76,77,79,80,81,82]) under different points of view. Their importance relies on being examples of nonhomogeneous domains which for a particular value of the parameter µ are Kähler-Einstein.…”
Section: Cartan-hartogs Domainsmentioning
confidence: 99%
“…Lemma 3.7. [19] Let (M, g) be a Kähler manifold. If (M, ag) is full Kähler immersion submanifold of CP n for any a > a 0 > 0 and if (M, g) and CP n are not relatives for any n < +∞, then (M, g) and CP n are not strongly relatives for any n < +∞.…”
Section: Almost Kähler-einstein Metricmentioning
confidence: 99%
“…Loi and Mossa [12] showed that a bounded homogeneous domains with a homogeneous Kähler metric and any projective Kähler manifold are not relatives in 2015. Zedda [19] gave a sufficient condition for a Kähler manifold are strongly not relative to any projective Kähler manifold in 2017. As an application, they got that the Bergman-Hartogs domain and Fock-Bargmann-Hartogs domain are strongly not relative to any projective Kähler manifold.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the work of Umehara, Di Scala and Loi [10] introduced the concept of "relatives" between two Kähler manifolds (i.e., they are said to be relatives if they share a common Kähler submanifold, otherwise, we say that they are not relatives) in 2010, and they proved that a bounded domain with its Bergman metric and a projective Kähler manifold with the restriction of the Fubini-Study metric are not relatives. For related problems, see Cheng, Di Scala and Yuan [6], Di Scala and Loi [9], Mossa [17] and Zedda [23].…”
Section: Introductionmentioning
confidence: 99%